Small but potent: GTPases as novel players on the neutrophils autophagy market. Issue 4 (20th July 2021) - Koziel, Joanna; Lech, Maciej
Graphical Abstract: GEM, small GTPase from the RGK family, serves as significant negative regulator of neutrophils' activity.